Assessment of personality disorder: a review of existing literature on psychological assessment - Sau, Meng Karn; Noor Aishah Rosli, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper reviews the literature on the use of psychological assessments to identify personality disorders (PD). The Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5) categorise ten types of personality disorders according to symptoms in Section II and according to traits in Section III. Structured interviews and self-report questionnaires being two methods used to assess personality disorders are discussed. The suggested structured interview instrument used during the clinical intake interview is the structured clinical interview for DSM 5 (SCID-5), and where personality disorder is detected, the structured clinical interview for personality disorder (SCID-5-PD) is used. Self-report instruments commonly used to assess pathology are the Personality Inventory for DSM-5 (PID-5), the Minnesota Multiphasic Personality Inventory 2 (MMPI-2), and the Million Clinical Multiaxial Inventory III (MCMI-III) are discussed. The paper ends with identifying some limitations arising from the use of assessments for identifying specific personality disorders(PDs), with suggestions for future research on the use of the PID-5 provided with the DSM-5 for the assessment.